Acacia Wood Bio-composites Towards Bio-Sustainability of the Environment - Rahman, Md Rezaur; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book investigates the enhancement of properties of acacia wood and its surface treatment for high strength bio-composites. It describes the tensile, flexural and impact strength, surface behaviour, morphological analysis, infrared spectral functional analysis, thermal properties analysis and dielectrical properties of acacia wood bio-composites. It reports efforts on the optimization of fabrication techniques to prepare acacia wood reinforced bio-composites based on PLA, PHA, Etc. The book also reports on environmental impact analysis of acacia wood bio-composites. A special chapter is dedicated to the nano-enhancement of acacia wood bio-composites and their possible use in applications in terms of sustainability and economics. .
Introduction of Various Types of Acacia Wood -- Acacia Wood and Its Surface Treatment for High Strength Bio-composites -- Optimization of Fabrication Technique to Prepare Acacia Wood Reinforced Bio-composites Based on PLA, PHA, Etc. -- Tensile, Flexural and Impact Strength of Acacia Wood Bio-composites -- Study of Surface Behaviour of Acacia Wood Bio-composites by Morphological Analysis -- Infrared Spectral Functional Group and Thermal Properties of Acacia Wood Bio-composites -- Environmental Impact Analysis of Acacia Wood Bio-composites -- Dielectrical Properties of Acacia Wood Bio-composites -- Effect of Nano-enhancement on Acacia Wood Bio-composites -- Possibility Usage of Acacia Wood Bio-composites in Applications and Appliances.
Keywords: Ceramic materials; Biomaterials; Sustainability; Ceramics; Biomaterials; Sustainability